Bovine serum albumin-based biomimetic gene complexes with specificity facilitate rapid re-endothelialization for anti-restenosis. (1st April 2022) - Hao, Xuefang; Gai, Weiwei; Ji, Feng; Zhao, Jiadi; Sun, Dandan; Yang, Fan; Jiang, Haixia; Feng, Yakai
Abstract: Re -endothelialization is a critical problem to inhibit postoperative restenosis, and gene delivery exhibits great potential in rapid endothelialization. Unfortunately, the therapeutic effect is enormously limited by inefficient specificity, poor biocompatibility and in vivo stability owing largely to the complicated in vivo environment. Herein, we developed a series of platelet membrane (PM) cloaked gene complexes based on natural bovine serum albumin (BSA) and polyethyleneimine (PEI). The gene complexes aimed to accelerate re-endothelialization for anti-restenosis via pcDNA3.1-VEGF165 (VEGF) plasmid delivery. Based on BSA and PM coating, these gene complexes exhibited good biocompatibility, stability with serum and robust homing to endothelium-injured site inherited from platelets. Besides, they enhanced the expression of VEGF protein by their high internalization and nucleus accumulation efficiency, and also substantially promoted migration and proliferation of vascular endothelial cells. The biological properties were further optimized via altering PEI and PM content. Finally, rapid recovery of endothelium in a carotid artery injured mouse model (79% re-endothelialization compared with model group) was achieved through two weeks' treatment by the PM cloaked gene complexes. High level of expressed VEGF in vivo was also realized by the gene complexes. Moreover, neointimal hyperplasia (IH) was significantly inhibited by the gene complexes according to in vivo study. The results verified the great potential of the PM cloaked gene complexes in re-endothelialization for anti-restenosis. Statement of significance: Rapid re-endothelialization is a major challenge to inhibit postoperative restenosis. Herein, a series of biodegradable and biocompatible platelet membrane (PM) cloaked gene complexes were designed to accelerate re-endothelialization for anti-restenosis via pcDNA3.1-VEGF165 (VEGF) plasmid delivery. The PM cloaked gene complexes provided high VEGF expression in vascular endothelial cells (VECs), rapid migration and proliferation of VECs and robust homing to endothelium-injured site. In a carotid artery injured mouse model, PM cloaked gene complexes significantly promoted VEGF expression in vivo, accelerated re-endothelialization and inhibited neointimal hyperplasia due to their good biocompatibility and superior specificity. Overall, the optimized PM cloaked gene complexes overcomes multiple obstacles in gene delivery for re-endothelialization and can be a promising candidate for gene delivery and therapy of postoperative restenosis. Graphical abstract: Image, graphical abstract